Higher education institutions, regional labour markets and population development - Lasse Sigbjørn Stambøl (European Regional Science Association (ERSA), 2011)
An important motivation to establish and develop higher education institutions across regions is to improve and restructure the regional labour markets toward higher education jobs, contribute to maintain the regional settlement patterns of the population generally and to increase the numbers of higher educated labour especially. This paper introduces a short description of the Norwegian regional higher education institution system, followed by analyses of the impact of higher education institutions on regional labour markets, labour and job mobility and population development featuring e.g. studies of the students' post graduate regional mobility and the regional ability of students to complete their graduation. Most of the analyses are based on data from individual registers covering the entire population, and partly organised as regional panel data. Tentative results suggest that regions that contain both university and high schools perform better than average on most indicators being analysed; especially, the ability to increase the number of higher educated labour, the return to the net increase of professionals at the higher education institutions on the numbers of regional higher educated labour, the ability to re-allocate jobs within firms from low to higher education jobs, higher than average net in-migration of population due to relatively low out-migration and stronger import of knowledge through in-migration than export of knowledge through out-migration, thus experiencing a strong regional "brain-gain". Furthermore, the regions where the higher education institute itself represents a minor part of the local higher educated labour market, perform mostly better than those regions where the higher education institute itself represents a medium or major part of the local higher educated labour market. Finally, the regions without higher education institutes mostly perform lower than average on most indicators, except the ability to create new jobs in new established firms. However, these regions also show higher than average closures of firms generally.
Keywords: 330